Topolectrical Circuit Correspondence Design of Polyacetylene - Albooyeh, Majid Reza; Sadeghi, Ali; Mohseni, Seyed Majid (Scientific reports, 2023)
In cis and trans geometrical configurations of the polyacetylene molecule, one-dimensional chain is constructed by attaching a number of identical –HC=CH– units one-by-one. We attach as many units as required to obtain the chain of the desired length. In case of a very long polyacetylene chain, which is practically considered infinite in length, a periodic unit is defined, so that its band structure would be calculable. Then, the electronic properties and topological properties of the chain can be predicted. Since experimental synthesis of single-layer polyacetylene chain has lots of limitations, in an alternative approach, emulation of a tight-binding model is used to describe the electron transfer in polyacetylene polymer chain. In case of either synthesis or testing the polyacetylene molecule, it is necessary to improvise a one-to-one correspondence between polyacetylene polymer and topological circuit, which is introduced for the first time in the present study. To this aim, the outputs of density functional theory calculations alongside with the calculations based on the physical chemistry formalisms are used. Here, we observed that the electronic response of the circuit is topologically sustained at frequencies where the coupling was pre-determined via high precision quantum system equivalent topolectrical circuit, as an alternative classical system, to study electron transfer of trans -polyacetylene polymer quantum chain by the precision of one-electron.